2019
DOI: 10.26508/lsa.201900488
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-8B controls basal body function and flagellum formation and is key to malaria transmission

Abstract: Eukaryotic flagella are conserved microtubule-based organelles that drive cell motility. Plasmodium, the causative agent of malaria, has a single flagellate stage: the male gamete in the mosquito. Three rounds of endomitotic division in male gametocyte together with an unusual mode of flagellum assembly rapidly produce eight motile gametes. These processes are tightly coordinated, but their regulation is poorly understood. To understand this important developmental stage, we studied the function and location o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(154 citation statements)
references
References 63 publications
23
120
0
Order By: Relevance
“…The loss of kinesin-5 may have been compensated for by the over-expression of another member of the kinesin family, therefore we analysed the transcript level of kinesin-8B, kinesin-8X and kinesin-13 in gametocytes of Δ kinesin-5 parasites. These kinesins are highly expressed in gametocytes and have important role during male gametogony [23,30]. We found that the kinesin-13 transcript level was significantly upregulated ( Fig.…”
Section: Pbkinesin-5 Is Dispensable For Cell Division During the Diffmentioning
confidence: 66%
See 3 more Smart Citations
“…The loss of kinesin-5 may have been compensated for by the over-expression of another member of the kinesin family, therefore we analysed the transcript level of kinesin-8B, kinesin-8X and kinesin-13 in gametocytes of Δ kinesin-5 parasites. These kinesins are highly expressed in gametocytes and have important role during male gametogony [23,30]. We found that the kinesin-13 transcript level was significantly upregulated ( Fig.…”
Section: Pbkinesin-5 Is Dispensable For Cell Division During the Diffmentioning
confidence: 66%
“…The transgenic parasites also produced gametocytes in mice, and therefore next we analysed male and female gametocyte differentiation following activation in the exflagellation/ookinete medium that mimics the mosquito gut environment. Male and female gametes emerge from the infected erythrocyte, and in the case of male gamete development this is preceded by three rapid rounds of genome duplication, resulting in eight flagellate male gametes [22,23]. There was no defect in male gamete exflagellation for either of the Δ kinesin-5 parasite clones, with the same exflagellation frequency as WT-GFP parasites ( Fig.…”
Section: Pbkinesin-5 Is Dispensable For Cell Division During the Diffmentioning
confidence: 99%
See 2 more Smart Citations
“…Current evidence suggests that certain canonical cell-cycle checkpoints are absent 16 . For example, compounds that interfere with mitotic spindle formation do not prevent DNA replication proceeding 17,18 , while spindle formation is not affected in a mutant that is unable to replicate DNA 18,19 . Recently, we observed that proteins involved in DNA replication and cytoskeletal reorganisation are phosphorylated during the first seconds of gametogony 20 .…”
Section: Introductionmentioning
confidence: 99%